The working hours of immigrants in Germany: Temporary versus permanent - Martin Kahanec; Michael P. Shields (IZA Journal of Migration, 2013)
Migration is often viewed as an investment decision. Temporary migrants can be expected to invest less in accumulating human capital specific to the host country. Instead, they work more hours in order to accumulate savings and invest in financial capital that can be transferred back to their country of origin upon return. In this paper, using German panel data, we explore how temporary migrants differ from permanent migrants in their labor supply decisions and behavior. After correcting for endogeneity bias, male temporary migrants are found to work more hours than permanent ones. The effect for females is statistically insignificant.
Keywords: J22; J61; F22; 330; migration; temporary migrants; labor supply; Germany